Strategi Guru dalam Pembelajaran PJOK untuk Anak Tunagrahita Kelas 8 SLB Negeri 1 Demak - Rohman, Andika Satriya Kurniya; Yuwono, Cahyo (Indonesian Journal for Physical Education and Sport, 2023)
he background of this research is that researchers want to know the teacher's strategy in teaching PJOK for mentally retarded children at SLB Negeri 1 Demak. The purpose of this study was to find out the strategies used by teachers in teaching PJOK mentally retarded children at SLB Negeri 1 Demak. The type of research used in this research is qualitative research with a descriptive approach. Data collection techniques are observation, interviews and documentation. The results of the study show that the teacher's strategy in teaching mentally retarded children. Sequence of learning activities, praying, providing learning information, warming up, core activities, and after the main activities the teacher immediately closes learning. In the results of observing the method used by the teacher using the lecture method. In addition to the method, the learning model that is applied uses a direct learning learning model. The learning media used by the teacher uses simplified media, is easy to use, and is familiar to students. Learning is carried out on Wednesdays with an allocation of 2 x 35 minutes of learning time. The conclusions of the research, before learning the teacher prepares the students, the method used is the lecture method and the learning model used is the direct learning model. The media used uses simplified media, learning is held once a week.